The direct and indirect influence of brand image, brand experience, and brand personality on brand loyalty - Mabkhot, Hashed Ahmad Nasser (2016)
The objective of this study is to investigate the relationships between brand image (BI), brand experience (BE), brand personality (BP), and brand loyalty (BL) of automobile local brands in Malaysia and also determining the mediating effect of brand satisfaction (BS) and brand trust (BT) on those relationships. This study is embarked on the fact that only a few studies have examined how brand image, brand experience, brand personality, brand satisfaction, and brand trust contribute towards the emergence of brand loyalty. Based on a theoretical consideration, a model was proposed and 17 hypotheses were formulated. Questionnaires were used to collect data. A total of 330 usable responses were received from respondents in the northern part of Malaysia, (Kedah, Penang, and Perlis). Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed in the data analysis. The findings reveal significant relationships between brand image and brand loyalty, and between brand experience and brand loyalty. However, this study does not find any significant relationships between brand personality and brand loyalty. This study observes that brand satisfaction mediates both the relationships between brand image, brand personality, and brand loyalty. In addition, brand trust mediates the relationships between brand personality and brand loyalty. However, brand satisfaction does not mediate the relationships between brand experience and brand loyalty. No significant mediation is observed of brand trust on the relationships between brand image, brand experience, and brand loyalty. The significance of this study can be seen in the incorporation of brand satisfaction and brand trust as the mediating tools to explain the relationships between brand image, brand experience, brand personality, and brand loyalty. The study concludes with a discussion on the contributions, limitations as well as suggestions for future research